Genomic profiling and precision medicine in complex ameloblastoma. Issue 4 (16th January 2023) - Gates, James C.; Clark, Allison P.; Cherkas, Elliot; Shreenivas, Aditya V.; Kraus, Dennis; Danzinger, Natalie; Huang, Richard S. P.; Johnson, Jennifer; Ross, Jeffrey S.
Abstract: Background: Ameloblastoma may present a significant treatment challenge in the locally advanced, recurrent and metastatic setting. Comprehensive genomic profiling (CGP) can identify targetable genomic alterations to aid in treatment. Methods: Ameloblastoma samples were sequenced using hybrid‐capture based sequencing. A systematic literature review was performed to examine outcomes in studies employing targeted treatment in ameloblastoma. Results: We reviewed 14 cases of Ameloblastoma using CGP. There were six patients with activating BRAF mutations, five with PIK3CA, five with SMO, four with FGFR2, one with EGFR, and one with ROS1 . All cases were MSI stable and the median TMB was 2.5 mutations/Mb. A separate literature review of clinical outcomes in ameloblastoma showed a predominance of at least partial response to targeted treatment (7/12 cases). Conclusion: CGP is helpful in identifying specific driver mutations in patients with complex ameloblastoma. Targeted treatment has been employed with success in achieving treatment response.